2016
DOI: 10.1021/acs.jpcc.6b10325
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Dependence of Exciplex Decay Rate on Through-Space Separation Distance between Porphyrin and Chemically Converted Graphene

Abstract: A series of chemically converted graphenes (CCGs) covalently functionalized with multiple zincporphyrins (ZnPs) through tuned lengths of linear oligo-p-phenylene bridges (ZnP-ph n -CCG, n = 1−5) were prepared to address the bridge length effect on their photodynamics. Irrespective of the bridge length, photoexcitation of ZnP-ph n -CCG led to exclusive formation of an exciplex state, which rapidly decayed to the ground state without yielding the completely charge-separated state. The notable dependence of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…e) Dependence of the exciplex decay rate constant ( k ) on the edge‐to‐edge separation distance ( R ee ) in semilogarithmic representation. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Intraconjugate Excited‐state Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…e) Dependence of the exciplex decay rate constant ( k ) on the edge‐to‐edge separation distance ( R ee ) in semilogarithmic representation. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Intraconjugate Excited‐state Interactionsmentioning
confidence: 99%
“…Another internal electronic interaction is seen between photoexcited Por and graphene/CNT when a covalent bridge of one or several p ‐phenylene units is employed, namely a CT interaction that leads to the formation of an exciplex . This exciplex decays rapidly to the ground state rather than to the CS state, resulting in no contribution to photocurrent generation.…”
Section: Intraconjugate Excited‐state Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For exciplex formation, the distance between electron-donor and electron-acceptor molecules has to be very small, on the order of a few nanometers at most. [11][12][13] However, Nakanotani et al observed exciplex emissions derived from long-distance coupled donor and acceptor molecules with a 10 nm thick spacer layer, 14 and then, Chapran et al, Li et al, and Sych et al also observed similar exciplex emissions with a several nanometer spacer layer, using different types of donor and acceptor molecules. [15][16][17] Colella et al reported that donor and acceptor molecules diluted in a host matrix (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…To achieve synergistic effects of the combinations of porphyrins and 2D nanocarbons on their performances in the applications, the occurrence of efficient photoinduced energy transfer (EnT) or electron transfer (ET) from the attached porphyrins to the 2D nanocarbons or vice versa is of extreme importance. Systematic investigations on porphyrin–2D nanocarbon covalently linked systems revealed that their photodynamics is profoundly affected by the spacer structures that govern separation distances and mutual orientations between porphyrins and 2D nanocarbons 2224. However, 2D nanocarbons in the porphyrin-linked systems reported so far consist of complicated mixtures with a range of sizes, shapes, and defects of the sp 2 carbon network.…”
Section: Introductionmentioning
confidence: 99%